Ambrisentan therapy in pulmonary hypertension: clinical use and tolerability in a referral centre. (June 2014) - Condliffe, Robin; Elliot, Charlie A.; Hurdman, Judith; Sabroe, Ian; Billings, Catherine; Kiely, David G.; Hamilton, Neil
Introduction: Ambrisentan is an oral selective endothelin receptor antagonist licensed for use in pulmonary arterial hypertension (PAH). There are few data on clinical use and long-term tolerability in a wider range of patients with pulmonary hypertension (PH). Methods: All patients treated with ambrisentan over a 4-year period were identified. Baseline characteristics, liver function test (LFT) results and World Health Organization (WHO) functional class were retrieved from hospital databases. Results: 272 patients received ambrisentan between March 2009 and June 2013 (32% idiopathic PAH, 36% connective tissue disease PAH, 11% congenital heart disease PAH, 6% portopulmonary hypertension, 1% HIV PAH, 4% PH in association with lung disease, 8% chronic thromboembolic PH and 2% PH in association with sarcoidosis). 33.5% of patients received ambrisentan as monotherapy and 12% received ambrisentan as their initial PH therapy. 18% stopped treatment due to side effects and 12% stopped due to lack of efficacy. Oedema was the most common side effect leading to cessation of therapy, which occurred in 7% of patients. 57% of patients who discontinued ambrisentan due to side effects also discontinued other PAH therapies due to side effects previously or subsequently. Ambrisentan was discontinued in two (<1%) patients due to abnormal LFTs. The 3-year survival in congenital heart disease PAH, idiopathic PAH and systemic sclerosis-associated PAH was 80%, 62%, and 38%, respectively ( p = 0.003). Survival was superior in patients in whom WHO functional class improved in response to therapy. Conclusion: Ambrisentan is used as an initial therapy and as monotherapy in a minority of patients in a large UK PH referral centre. Discontinuation due to side effects, and especially oedema, was higher than reported in previous studies while discontinuation due to abnormal LFTs was very uncommon. A majority of patients who discontinued therapy due to side effects also previously or subsequently discontinued other PAH therapies. Improvement in WHO functional class was associated with superior survival.